A deterministic approach about collapse of organizations from Ibn-I Haldun to day - Demirtaş, Zülfü; Usta, Mehmet Emin (My University, 2011)
This research, aims to revise thoughts coming from past up to present expressed about life duration and deaths of organizations. Research framed in literature review model, our day's thinkers and views of Ibn Khaldun whose deterministic views about organizations deaths have firstly mentioned are issued. Ibn Khaldun handle state in organization sense and generally gives a-120-year-life span to the state. Our day's thinkers on the other hand, handle society and organizations placed in society. However, these thinkers refrain from determining a specific life span of organizations. These thinkers with this emphasize on reasons which enable to determine organizations' life spans and make this span longer.
Ibn-I Haldun'dan günümüze örgütlerin çöküsüne dair deterministik bir yaklasim
Keywords: Death of organizations; Entropy; Functionality; Ibn khaldun; Mukaddima; Organization; Organizational learning